Pakej pengarangan kertas soalan examination paper authoring package EPAP / Pang Yen Ping - Pang , Yen Ping (2004)
The Examination Paper Authoring Package (EPAP) is a web-based system that helps teachers and lectures in colleges and universities lo create examination papers online. The EPAP provides faster efficient, and yet secure way of examination papers creation that will reduce the lecturer's workload. EPAP provides three question types such as multiple choice question, structured question and essay question that enables lecturer to create questions easily. It also allows for the questions maintenance in which lecturer is allowed to edit the questions. The EPAP will organize the papers to be printed out for publishing purpose. Guided by the Waterfall with Prototyping model methodology, EPAP will be developed phase by phase together with the iterative prototyping to meet the user requirements. The EPAP will be developed on the multi-tier client/server, using ColdFusion technology and the ColdFusion Markup Language together with HTML, Javascripts. Microsoft SQL server will serves as database server in the EPAP that provide secure storage for the examination papers. The EPAP will be built within the limitation boundaries of the project. The constraints that limit the EP AP are stated in the project limitation. There are suggestions for future enhancements for the EPAP that will certainly result in better user experiences. However, during the course of the EP AP development, continuous efforts will be put in to fulfill the user requirements.